Practicing pragmatist aesthetics : critical perspectives on the arts - Małecki, Wojciech. (Value Inquiry Book Series, 2014)
This is the first collection in English devoted exclusively to pragmatist aesthetics. Its main aim is to employ the resources of that rich and exciting tradition in studying artistic phenomena such as film, sculpture, bio-art, poetry, the novel, cuisine, and various body arts. But it also attempts to provide a wider background for such studies by sketching the history of pragmatist reflection on the aesthetic and by discussing some of the main positions that this history has produced: the aesthetic conceptions of C.S. Peirce, William James, John Dewey, Joseph Margolis, Richard Shusterman (somaesthetics in particular), and others.